A diarylheptanoid compound from Alpinia officinarum Hance ameliorates high glucose-induced insulin resistance by regulating PI3K/AKT-Nrf2-GSK3β signaling pathways in HepG2 cells. (15th September 2022) - Zhang, Xu-guang; Liu, Ai-xia; Zhang, Yu-xin; Zhou, Ming-yan; Li, Xiang-yi; Fu, Ming-hai; Pan, Yi-peng; Xu, Jian; Zhang, Jun-qing
Abstract: Ethnopharmacological relevance: Alpinia officinarum Hance, a perennial natural medicine-food herb, has been traditionally used to treat colds, stomachache, and diabetes for thousands of years. 1, 7-Diphenyl-4E-en-3-heptanone (DPH5), a diarylheptanoid isolated from the rhizome of A. officinarum has been reported to be safe and to have antioxidant and hypoglycemic effects, suggesting its potential in the treatment of insulin resistance (IR). Aim of the study : Aim of to investigate the protective effect of DPH5 on IR and elucidate its underlying mechanism of action. Materials and methods: HepG2 cells were used as the research objects. Glucose uptake and reactive oxygen species (ROS) levels in high glucose–induced insulin-resistant HepG2 cells were assessed using flow cytometry. Glucose consumption and the levels of malondialdehyde (MDA) and superoxide dismutase (SOD) were analyzed using the corresponding assay kits. The expression of mRNA and proteins related to insulin signaling, glucose metabolism, and antioxidant factor, including insulin receptor substrate-1 (IRS1), phosphatidylinositol 3-kinase (PI3K), protein kinase B (AKT), translocation of glucose transporter-4, glycogen synthase kinase-3β (GSK3β), glucokinase (GCK), pyruvate kinase (PK), phosphoenolpyruvate carboxykinase (PEPCK), glucose-6-phosphatase (G6Pase), nuclear factor-erythroid 2 related factor 2 (Nrf2), heme oxygenase-1 (HO-1), NADPH quinoneoxidoreductase (NQO1), and glutathione peroxidase (GSH-Px) was determined using real-time quantitative polymerase chain reaction and western blotting. Furthermore, molecular docking was performed to determine the spatial mechanism of DPH5 on the key targets PI3K, AKT, Nrf2, and GSK3β. Results: DPH5 could improve IR that manifested as increased glucose uptake and glucose consumption in insulin-resistant HepG2 cells. Moreover, DPH5 could enhance antioxidant capacity by activating Nrf2/HO-1 elements, including increasing Nrf2, HO-1, SOD, NQO1, and GSH-Px expression and reducing MDA, ROS, and JNK levels, thereby improving oxidative stress and ultimately alleviating IR. Additionally, DPH5 could promote the expression of IRS1, PI3K, AKT, GSK3β, GCK, and PK, and downregulate the expression of PEPCK and G6pase, thereby accelerating glucose utilization and enhancing insulin sensitivity. The mechanism underlying the effect of DPH5 in alleviating IR was related to the PI3K/AKT- and Nrf2/HO-1-mediated regulation of the GSK3β signaling pathway, and the results were further confirmed using the specific inhibitors LY294002 and ML385. Results from molecular docking indicated that there were different regulatory sites and interacting forces between DPH5 and PI3K, AKT, Nrf2, and GSK3β; however, the binding force was relatively strong. Conclusions: DPH5 improved oxidative stress and glucose metabolism via modulating the PI3K/AKT-Nrf2-GSK3β pathway, thereby ameliorating IR. Overall, our findings suggest the potential of DPH5 as a natural medicine to treat type-2 diabetes mellitus. Graphical abstract: Image 1